Non-vitamin k antagonist oral anticoagulants in a European primary care physician survey - Claudio Cimminiello; Robert Hatala; Sami Pakarinen; Hernan Polo Friz; David Fitzmaurice; FD Richard Hobbs (BJGP Open, 2018)
Background: Familiarity and competency in the options for stroke prevention in atrial fibrillation (AF) and the role of non-vitamin K antagonist oral anticoagulants (NOACs) may vary among primary care physicians (PCPs) from different European countries. Aims: To investigate PCP views on prescribing and managing NOACs across Europe and identify perceived unmet needs. Design & setting: Web-based survey including PCPs with particular interest in cardiovascular medicine. Method: A questionnaire was drawn up, containing 10 questions on initiation and ongoing management of NOACs; use of AF stroke guidelines on NOACs and anticoagulant switching; and perceived information needs. Results: The overall response rate was 42%. The majority of PCPs declared they are responsible for and confident in both initiating and managing NOAC therapy. In some countries, PCPs are not able to initiate NOAC therapy due to administrative barriers (namely, Italy and Slovakia). No single set of guidelines is referred to across all countries and over a fifth of responders indicate they do not follow specific guidelines. The main learning needs reported were more related to initiation than to ongoing management of anticoagulant therapy. Conclusion: According to this self-assessment survey, the experience of most PCPs in management of different aspects of AF appears good and only some felt the need for further training. However, in the light of the importance of this topic as public health issue, intensified efforts aiming at better equipping PCPs to meet their key roles in an integrated service across Europe are overdue.